Labour Market Trends and Structures in ASEAN and the East Asia NIEs - Manning, Chris (Institutional Knowledge at Singapore Management University, 1990)
The paper reviews the literature on labour markets in the region with special emphasis on the impact of economic growth and structural change on employment and wages. It deals with labour supply trends, employment creation outside agriculture (especially export orientated industrialization and new high-tech industries), labour absorption in agriculture, wage differentials and the functioning of rural and urban labour markets. The creation of efficient and equitable labour market institutions and labour market flexibility have emerged as dominant issues in the NIEs. In the ASEAN-4, because of concentration of employment in low productivity and low wage jobs and underutilization of labour, the rate of modern sector labour absorption remains the major policy concern.